(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article analyzes the effectiveness of the "process-oriented approach" in improving the writing skills of secondary school students learning English as a foreign language. Unlike the "product-oriented" method commonly used in Uzbek schools, this approach involves the implementation of writing in stages (planning, drafting, editing, and revising). The results of the study show that this method develops not only students’ written speech, but also their creative thinking and self-editing skills.